The community of practice as a place of prevention: the value of collective knowledge in occupational safety - Gilardi, Luisella; Marino, Maurizio; Fubini, Lidia; Pasqualini, Osvaldo; Ferro, Elisa; Santoro, Silvano; Tosco, Eleonora; Bena, Antonella; Coffano, Maria Elena (La Medicina del Lavoro, 2017)
Background: Occupational Health and Safety (OSH) inspectors of the Health Units of Piedmont Region wrote 47 case histories based on data gathered from injury investigations as part of the project “From the injury investigation reports to case histories: creation of a collection of case histories on occupational injuries”. Afterwards a Community of Practice (CoP) was initiated with the aim of sharing recommendations for prevention of occupational injuries. Objective: The aims of the article are: 1) to describe the implementation process of the CoP; 2) to evaluate the benefits of CoP regarding the improvement of professional practice of OSH inspectors. Methods: Two injury case histories were peer reviewed during each meeting of the CoP. A focus group was set up to evaluate benefits of CoP. Seven OSH inspectors participated in this focus group. Results: Eight CoP meetings were organized and about 70 OSH inspectors participated. Fourteen stories were peer reviewed and eight were published on www.dors.it. Operators involved in the focus groups reported that the main reasons for participation in the CoP were the need to compare and tackle new challenges. The criticalities are tied to the turnover of the participants and to the lack of recognition by management. Most of the operators felt it was too early to include professionals such as Workers’ Safety Representatives and Prevention and Safety Service Managers in the CoP due to their different professional roles. Conclusions: OSH inspectors reported professional benefits of CoP experience. We believe that this approach might be transferred, integrated and developed in other regions and included in the next national prevention plan.